2020
DOI: 10.1002/bies.201900208
|View full text |Cite
|
Sign up to set email alerts
|

Ric‐8A, a GEF, and a Chaperone for G Protein α‐Subunits: Evidence for the Two‐Faced Interface

Abstract: Resistance to inhibitors of cholinesterase 8A (Ric‐8A) is a prominent non‐receptor GEF and a chaperone of G protein α‐subunits (Gα). Recent studies shed light on the structure of Ric‐8A, providing insights into the mechanisms underlying its interaction with Gα. Ric‐8A is composed of a core armadillo‐like domain and a flexible C‐terminal tail. Interaction of a conserved concave surface of its core domain with the Gα C‐terminus appears to mediate formation of the initial Ric‐8A/GαGDP intermediate, followed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…The G protein signaling cycle is regulated by several proteins, including GEFs (e.g., GPCRs, GIV/Girdin, or Ric-8A) and GTPase-activating proteins [GAPs; e.g., regulators of G protein signaling (RGS)]. 48 , 49 , 50 , 51 , 52 As our data support slow AHD closing enabled by the long-lived intermediate state of Gαs after GTPγS binding, we searched for an AHD-binding protein that might regulate the AHD closing kinetics. To this end, we employed Y2H library screening with the Gαs AHD as bait and identified melanoma-associated antigen D2 (MAGE D2, NM_014599) as a novel Gαs AHD-binding protein ( Figure S8 A).…”
Section: Resultsmentioning
confidence: 99%
“…The G protein signaling cycle is regulated by several proteins, including GEFs (e.g., GPCRs, GIV/Girdin, or Ric-8A) and GTPase-activating proteins [GAPs; e.g., regulators of G protein signaling (RGS)]. 48 , 49 , 50 , 51 , 52 As our data support slow AHD closing enabled by the long-lived intermediate state of Gαs after GTPγS binding, we searched for an AHD-binding protein that might regulate the AHD closing kinetics. To this end, we employed Y2H library screening with the Gαs AHD as bait and identified melanoma-associated antigen D2 (MAGE D2, NM_014599) as a novel Gαs AHD-binding protein ( Figure S8 A).…”
Section: Resultsmentioning
confidence: 99%
“…The G-protein signaling cycle is regulated by several proteins, including GEFs (e.g., GPCRs, GIV/Girdin, or Ric-8A) and GTPase-activating proteins [GAPs; e.g., regulators of G protein signaling (RGS)] (Kach et al, 2012; Kalogriopoulos et al, 2019; Siderovski and Willard, 2005; Srivastava and Artemyev, 2020; Srivastava et al, 2019). As our data support slow AHD closing enabled by the long-lived intermediate state of Gαs after GTPγS binding, we searched for an AHD-binding protein that might regulate the AHD closing kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the Ric-8A function in a given system, the structures can represent either the GEF complex intermediate with an empty-pocket for nucleotide binding or the folding intermediate of Gα during its biosynthesis. The Ric-8A/Gα complexes reveal two remarkable features: a large displacement of the α5-helix of Gα from the β-sheet cradle of the Ras-like domain, and a unique interaction of the C-terminal helix of Ric-8A with the switch II/α3-helix region of Gα ( Srivastava and Artemyev, 2019 , 2020 ; McClelland et al, 2020 ; Seven et al, 2020 ). The interaction of Ric-8A with the C-terminus/α5-helix of Gα is central to both the GEF and the chaperone activity.…”
Section: Discussionmentioning
confidence: 99%
“…When Ric-8A acts as a chaperone, this interaction induces the folding of the α5-helix outside the β-sheet cradle of partially folded Gα ( Srivastava et al, 2019 ; McClelland et al, 2020 ). The interaction of the C-terminal helix of Ric-8A with the switch II/α3-helix region of Gα likely promotes GTP-binding to Gα thereby concluding either the GEF or the chaperone cycle of Ric-8A ( Srivastava and Artemyev, 2019 , 2020 ; McClelland et al, 2020 ; Seven et al, 2020 ). We demonstrated that Ric-8A is expressed throughout the retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation